Correlation of skin moisture and serum urea level with dermatology life quality index in patients with chronic kidney disease on hemodialysis: A cross-sectional study - Dalimunthe, Dina A.; Hazlianda, Cut P.; Lubis, Flora M.; Sinaga, Riana M.; Salim, Stephanie (Narra Sains Indonesia, 2024)
Chronic kidney disease (CKD) is a global health concern, with a 10% global prevalence. Its prevalence may further increase in the coming decades, thereby increasing the risk of uremic xerosis. Approximately 50–90% of patients with CKD have xerosis, leading to pruritus that affects their quality of life due to sleep disturbances, anxiety, and depression. However, the exact mechanisms underlying xerosis in CKD remain unknown. The aim of this study was to assess the correlation of serum urea levels and skin moisture with quality of life in patients with CKD. This cross-sectional study was conducted at the Universitas Sumatera Utara Hospital from March to December 2023. Patients with CKD aged ≥18 years who were undergoing hemodialysis for at least 3 months were included in this study. A translated Dermatology Life Quality Index (DLQI) questionnaire was employed to assess the patient’s quality of life. Serum urea levels and skin moisture were determined using venous blood and the Skin Moisture Checker MY-808S tool, respectively. In total, 67 patients with CKD, including 61.2% males and 32.8% individuals aged >60 years, were enrolled in this study. The mean age was 52.73±13.08 years. The mean serum urea levels, skin moisture, and DLQI scores were 154.08±49.10 mg/dL, 36.22±2.34%, and 4.67±3.98, respectively. No difference in DLQI scores was observed between normal and high serum urea levels or between dry and normal skin moisture levels (p=0.156 and p=0.804, respectively). Spearman’s correlation analysis revealed no correlation between serum urea levels and average skin moisture with DLQI (p=0.600 and p=0.353, respectively), indicating that multiple factors contribute to the dermatological quality of life in patients with CKD. Notably, DLQI in patients with CKD can be simultaneously affected by multiple factors, such as diverse sociodemographic backgrounds, coping mechanisms, and the impact of symptoms associated with CKD, other than serum urea levels and average skin moisture. Therefore, adopting a multifactorial and individualized approach is crucial to improving the DLQI scores of patients with CKD.